The Role Of Science Teachers In Increasing Students' Learning Motivation In The Independent Curriculum Era According To Behavioristics - Sujana, R. M. Helmy; Ekawati, Selviana; Ningsih, Zahra; Mahardika, I Ketut (PT. Hafasy Dwi Nawasena, 2024)
In the era of the Merdeka Curriculum, which is integrated with technological developments, requires a science teacher to carry out his duties professionally. One part of the teacher's professionalism is understanding learning theory. Behavioristic learning theory, which tends to be teacher-centered, is still often used by teachers even though the curriculum has changed because the application of this theory in learning is still relevant and works well. One of the results of research conducted by Yuliani (2020) entitled “Development of E-Book Learning Media with a Behavioristic Approach to Science Subjects for Class IX Students of SMP 24 Banjarmasin” states that the behavioristic approach shows a positive influence on improving student achievement. The results of analyzing student learning using the N-Gain test are 0.8 (included in the high classification). The results of this study indicate that the behavioristic flow in the era of the independent curriculum is able to increase learning motivation even though the application of behavioristic flow tends to be teacher-centered. The urgency of behavioristic flow in the implementation of learning is to maximize the role of teachers, especially in improving student discipline.